A Novel Noninvasive Model of Endometriosis for Monitoring the Efficacy of Antiangiogenic Therapy - Becker, Christian M. (American Society for Investigative Pathology, 2006)
Endometriosis, the presence of ectopic endometrial tissue, is a common disease associated with high morbidity and socioeconomic problems. Angiogenesis, the formation of new blood vessels, plays an important role in the formation and growth of endometriotic lesions. We have created a novel, noninvasive model to monitor the growth of these lesions and the associated angiogenesis in vivo. First, we generated luciferase-expressing transgenic mice by inserting the human ubiquitin C promoter coupled to the firefly luciferase reporter. Injection of luciferin in these mice causes full-body bioluminescence, which can be detected using a low-light CCD camera. Endometrial tissue from these transgenic mice was surgically implanted into nonluminescent recipients. Bioluminescence of lesions was noninvasively imaged after intravenous or intraperitoneal injection of luciferin. Transabdominal luminescence compared well with the location of the transgenic endometriotic lesions, and lesion size correlated with the intensity of luminescence. Systemic treatment with the angiogenesis inhibitors caplostatin and endostatin peptide mP-1 delayed and suppressed the onset and intensity of the luminescent signal. Caplostatin suppressed the growth of endometriotic lesions by 59% compared with controls. This novel, noninvasive model of endometriosis provides a means to study early angiogenesis in vivo and to monitor endometriotic growth and the efficacy of systemic antiangiogenic therapy.